COSMOS brightest group galaxies: III. evolution of stellar ages - Gozaliasl, Ghassem; Finoguenov, A.; Babul, A.; Ilbert, O.; Sargent, M.; Vardoulaki, E.; Faisst, A. L.; Liu, Z.; Shuntov, M.; Cooper, O.; Dolag, K.; Toft, S.; et al. (Astronomy and astrophysics, 2024)
The unique characteristics of the brightest group galaxies (BGGs) serve as a link in the evolutionary continuum between galaxies such as the Milky Way and the more massive brightest cluster galaxies found in dense clusters. This research investigates the evolution of the stellar properties of BGGs over cosmic time (z = 0.08 − 1.30), extending the work from our prior studies. We analyzed the data of 246 BGGs selected from our X-ray galaxy group catalog within the COSMOS field, examining stellar age, mass, star-formation rate (SFR), specific SFR, and halo mass. We compared observations with the Millennium and Magneticum simulations. Additionally, we investigated whether stellar properties vary with the projected offset from the X-ray peak or the hosting halo center. We evaluated the accuracy of SED-derived stellar ages using a mock galaxy catalog, finding a mean absolute error of around 1 Gyr. Interestingly, the observed BGG age distributions exhibit a bias toward younger intermediate ages compared to both semi-analytical models and the Magneticum simulation. Our analysis of stellar age versus mass unveils intriguing trends with a positive slope, hinting at complex evolutionary pathways across redshifts. We observed a negative correlation between stellar age and SFR across all redshift ranges. We employed a cosmic time dependent main sequence framework to identify star forming BGGs and find that approximately 20% of BGGs in the local universe continue to exhibit characteristics typical of star forming galaxies, with this proportion increasing to 50% at z = 1.0. Our findings support an inside-out formation scenario for BGGs, where older stellar populations reside near the X-ray peak and younger populations at larger offsets indicate ongoing star-formation. The observed distribution of stellar ages, particularly for lower-mass BGGs in the range of 1010−11 M⊙, deviates from the constant ages predicted by the models across all stellar mass ranges and redshifts. This discrepancy aligns with the current models’ known limitations in accurately capturing galaxies’ complex star-formation histories.
Online verfügbar: , Artikelversion:
Gesehen am 03.06.2025